The Economic Impact of Torre De Moncorvo’s Wine and Taste Festival - Joana FERNANDES; Aida CARVALHO; Victor MOREIRA (Communications of International Proceedings, 2020)
An event can exist at a particular time and place, specifically prepared and developed with a certain purpose and for a target audience. According to the purpose and other factors, one can categorize events in a multitude of classifications. In this sense, this paper will focus on food and wine touristic events.A touristic event has the potentiality to attract new people to a region and, as such, attract new money, enhancing not only the economic activity of the region, but also its visibility, its image, and the diffusion of local culture. An event moves people, creating jobs and increasing the revenues for a country or a region, and can also develop the destinies’ notoriety and increase the demand in low seasons.This potential economic enhancement and cultural visibility is increasingly appealing for local and regional public and private entities as part of the economic and promotional development strategy of the region. As such, it is relevant to understand the annual Vinho & Sabor Douro, a wine and taste festival, that happens in Torre de Moncorvo, regarding its economic impact and how it promotes local culture and products.A survey was conducted in order to estimate the behaviour of exhibitors and visitors of the event. With the data collected it was possible to understand the importance of this event regarding exhibitors’ revenues, visitors’ preferred products, and how much the visitors spent, which allowed to estimate the economic impact of the event for the region.
Keywords: Wine and Food Festival; Cultural Tourism; Economic Impact; Torre de Moncorvo.